Seismic signals from large, tabular icebergs drifting along the Dronning Maud Land coast, Antarctica, and their significance for iceberg monitoring. Issue 227 (2015) - Pirli, Myrto; Matsuoka, Kenichi; Schweitzer, Johannes; Moholdt, Geir
Abstract: In this study, we analyze a large dataset of seismic signals, recorded by station TROLL in Dronning Maud Land, Antarctica. The signals, recorded in April–December 2012, came from sources near the edge of the ice shelves, at distances of 230–500 km from TROLL. The sources, which moved westward with time, could be associated with four large, tabular icebergs, drifting between 15° E and 8° W. Combining the seismological data with information from satellite remote sensing, we find that one-third of the signals can be attributed to individual icebergs. The trajectories of three of the associated icebergs are known through iceberg-tracking databases, whereas the fourth, a fragment of one of the other three, is untracked, and only scarce information is available from satellite imagery. The observed seismic signals exhibit a wide variety of frequency characteristics, from unstructured episodes to occurrences of iceberg harmonic tremor. Although we are not able to determine the exact cause of the signals, we classify them into five classes on a phenomenological basis. This study demonstrates the potential of regional seismic networks for iceberg monitoring as supplementary resources to information obtained with remote-sensing technologies.